American black widow : the shocking true story of a preacher's wife turned killer - Olsen, Gregg (Grand Central Publishing, 2024)
"From the #1 New York Times bestselling author of If You Tell comes the chilling, unputdownable story of Sharon Nelson, the minister's wife whose two husbands mysteriously ended up dead. Colorado, 1976. When Reverend Mike Fuller and his beautiful wife Sharon arrive in the sleepy town of Rocky Ford, local residents think something's off about the new couple. The God-fearing minister is gruff and cold, while charismatic Sharon has her husband wrapped around her finger. It isn't long before Sharon is charming her husband's congregation, and finds herself in a tryst with local, married optometrist Perry Nelson. After the affair ends both their marriages, Sharon and Perry tie the knot. But shortly afterwards, Perry disappears. When his body is shockingly discovered the bottom of a canyon, his death is ruled an accident, allowing grieving widow Sharon to claim his substantial life insurance.Trying to move on from the tragedy, Sharon soon remarries fireman Glenn Harrelson. But when the charred remains of Glenn's body are discovered with two bullet holes in his skull, the police can't help but question if both men dying in such mysterious circumstances is one coincidence too many..." --